Increasing Chinese EFL Learners’ Grit: The Role of Teacher Respect and Support - Shen, Yumin; Guo, Hongyu (Frontiers in Psychology, 2022)
Owing to the pivotal role of grit in scholastic success, factors that help learners become gritty are worth to be studied. Accordingly, this research sought to inspect the impact of teacher respect and teacher support on Chinese EFL learners’ grit. In doing so, three reliable measures of the variables were sent to 613 Chinese EFL learners. Using Spearman correlation tests, strong connections were discovered between teacher respect, teacher support, and Chinese EFL learners’ grit. Multiple regression analysis was then performed to inspect the role of teacher respect and teacher support in increasing Chinese EFL learners’ grit. As a result, both teacher respect and teacher support were found to be highly influential in increased learner grit. The limitations and implications are discussed.